Применение метода многомасштабного моделирования в исследовании электротехнических систем - Кучерявая, И.Н. (Технічна електродинаміка, 2011)
The article is a review of research works devoted to computer multi-scale modeling in the field of electrical engineering. The method of multi-scale modeling is described. The ways of its realization are explained. A number of the most typical classes of problems for using the method are presented. Among the problems are numerical investigation of electric field and computation of effective characteristics for composite dielectric materials; investigation of electromagnetic processes and determination of parameters for power transformers at high frequency; study of electromagnetic and thermal processes for induction heating installations; analysis of processes under the action of external electromagnetic field for biological and nano-sized systems. The advantages and some difficulties in the utilization of the method of multi-scale modeling are noted.